A Rehabilitative Justice Pathway for War-Traumatized Offenders Caught in the Military Misconduct Catch-22. Issue 1 (January 2018) - Seamone, Evan; Sreenivasan, Shoba; McGuire, James; Smee, Dan; Clark, Sean; Dow, Daniel
The United States and Canada, among others, have recognized that "misconduct stress behaviors" can be a "hidden" by-product of war-zone deployments. The American military's paradigm of punishment over treatment creates a "military misconduct Catch-22, " in which the service member's treatment need is identified as a result of, or only after, violations of military law. Civilian society then bears the justice, familial, and social costs of the military's failure to address combat stress–based misconduct. As an alternative to existing punitive military pathways, we propose a rehabilitative justice pathway that builds on the successes of civilian criminal justice mental health courts—to be implemented during active duty service, before separation from the Armed Forces. The approach, predicated on the circumstances of each case, promotes resilience, honorable discharge, and successful reintegration of service members into society.